Development of product costing in Lithuania (1918–2019) - Tamulevičienė, Daiva; Mackevičius, Jonas (Buhalterinės apskaitos teorija ir praktika, 2019)
Appropriate product costing helps not only to estimate the cost of production correctly but also to evaluate the activity results, forecast product prices, make reasonable economic decisions. The article analyses the development of product costing in Lithuania from 1918 to 2019. The following stages of development of product costing were distinguished: 1) between the world wars when Lithuania was independent and during the Second world war (1918–1944); 2) during the years of Soviet occupation (1944–1990); 3) after reinstating the independence of Lithuania (1990–2019). The most important provisions of normative documents related to product costing of every stage were analysed, opinions, statements and suggestions how to improve product costing by different Lithuanian authors were evaluated.